Optimasi Proses Transaksi Jual Beli Bahan Pangan Rempah-Rempah melalui Sistem Informasi Pencatatan Berbasis Website pada Toko Stella Jaya - Ferdinand Rustjo, Reandy (Green Publisher Indonesia, 2024)
Information technology has become a crucial element in business management, especially in financial recording. Many small to medium-sized businesses, such as Toko Stella Jaya, still rely on manual systems that cause various problems, including data loss, recording errors, and low efficiency. Manual bookkeeping at Toko Stella Jaya results in inaccuracies in stock recording and difficulties in producing timely financial reports. To overcome these obstacles, a web-based system is needed that can automate the process of recording sales, making notes, inventory management, and preparing financial reports. The proposed system is equipped with supplier data management features, real-time sales recording, automatic note generation, and financial reports, which are expected to increase operational efficiency and simplify the bookkeeping management of Stella Jaya Store. This research aims to design a technological solution that not only reduces the risk of data loss, but also increases accuracy and speed in business financial management.